Incomplete markets and trade - Paul Willen (Federal Reserve Bank of Boston, 2004)
In this paper, we show that incomplete markets lead to trade imbalances. We use a two-period general equilibrium model with countries composed of heterogeneous households. We look at a world where, when markets are complete, countries engage in balanced trade; and we show that when some of those markets are absent, trade imbalances emerge. Market incompleteness across countries causes trade imbalances because national income in some countries is more sensitive to risky asset payoffs than in others. Market incompleteness within countries causes trade imbalances because superior risk-sharing in one country leads to a lower precautionary demand for saving.
Keywords: D52; F30; 330